2007
DOI: 10.1021/bi061540x
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Amyloidogenic Effect Is Exerted against Alzheimer's β-Amyloid Fibrils in Vitro by Preferential and Reversible Binding of Flavonoids to the Amyloid Fibril Structure

Abstract: How various anti-amyloidogenic compounds inhibit the formation of Alzheimer's beta-amyloid fibrils (fAbeta) from amyloid beta-peptide (Abeta) and destabilize fAbeta remains poorly understood. Using spectrophotometry, spectrofluorometry, atomic force microscopy, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and surface plasmon resonance (SPR), we investigated the anti-amyloidogenic effects of five flavonoids on fAbeta in vitro. Oxidized flavonoids generally inhibited fAbeta(1-40) formation signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 43 publications
(61 reference statements)
4
113
0
Order By: Relevance
“…74 Besides EGCG, other flavonoids have also shown antiamyloidogenic properties especially myricetin, that exerts an antiamyloidogenic effect in vitro by preferentially and reversibly binding to the amyloid fibril structure of Aβ, rather than to Aβ monomers. 75,76 Overall, these studies suggest that certain flavonoids are able to disrupt fibrillization by leading to the production of off-target Aβ oligomers, function as BACE-1 inhibitors or act by enhancing ADAM10 activity, consequently reducing Aβ production (Figure 3). However, more studies are needed to discover which flavonoid structures have the greatest beneficial potential and their underlying mechanisms of action.…”
Section: ■ Flavonoidsmentioning
confidence: 98%
“…74 Besides EGCG, other flavonoids have also shown antiamyloidogenic properties especially myricetin, that exerts an antiamyloidogenic effect in vitro by preferentially and reversibly binding to the amyloid fibril structure of Aβ, rather than to Aβ monomers. 75,76 Overall, these studies suggest that certain flavonoids are able to disrupt fibrillization by leading to the production of off-target Aβ oligomers, function as BACE-1 inhibitors or act by enhancing ADAM10 activity, consequently reducing Aβ production (Figure 3). However, more studies are needed to discover which flavonoid structures have the greatest beneficial potential and their underlying mechanisms of action.…”
Section: ■ Flavonoidsmentioning
confidence: 98%
“…56 For the effect on AD pathogenesis, there have been reports that RA reduces A␤-induced neurotoxicity 57,58 and protects against reactive oxygen species induced by A␤ in cell culture experiments. 58 In intracerebroventricular A␤ [25][26][27][28][29][30][31][32][33][34][35] injection mice model studies, i.p. injection of RA prevents memory impairment and A␤-induced neurotoxicity by scavenging ONOO Ϫ .…”
Section: Phenolic Compounds Prevent Ad Pathology 2561mentioning
confidence: 99%
“…26 To date, it has been reported that various compounds inhibit the formation and extension of A␤ fibrils, as well as destabilizing A␤ fibrils in vitro. 19,20,[27][28][29][30][31][32][33][34][35][36] Among the reported compounds, several phenolic compounds, such as wine-related polyphenols (myricetin (Myr), morin, and tannic acid, and so on), curcumin (Cur), ferulic acid (FA), nordihydroguaiaretic acid (NDGA), and rosmarinic acid (RA) had especially strong anti-A␤ aggregation effects in vitro. Furthermore, it was shown recently that a commercially available grape seed polyphenolic extract, MegaNatural-Az, inhibited fibril formation, protofibril formation, and oligomerization of A␤.…”
mentioning
confidence: 99%
“…Wine-related polyphenols isolated by high performance liquid chromatography have been shown to inhibit the formation of A␤ fibrils as well as to dissociate preformed fibrils by preferentially and reversibly binding to these structures (23)(24)(25). For example, tannic acid, myricetin, morin, and quercetin inhibited fibril formation by Ͼ70% (23,24).…”
mentioning
confidence: 99%